Collective Victimhood Narratives in Legislative Speeches from the United States and Northern Ireland - Craig, Callum Mervyn (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2025)
In this thesis, I examine the use of victimhood narratives by legislators in the United States Congress and the Northern Ireland Assembly. Collective victimhood is a form of highly emotive and moral rhetoric which depicts groups as having been unjustly and intentionally harmed by another. As victimhood becomes increasingly important in the U.S. context and remains central to post-conflict Northern Irish politics, understanding when, why, and how elites use these narratives takes on importance for those seeking to understand polarization, radicalization, and reconciliation. I utilize an array of computational text analysis methods to detect and classify millions of speeches across both cases and as the basis for my analyses. In the U.S. chapter, two main analyses are conducted. First, I assessed the relationship between constituency, individual, and geographical characteristics and legislators use of victimhood narratives. I find that the identity of legislators and ideological positions have significant effects on the use of victimhood narratives. Second, I employ a difference-in-differences design to evaluate the impact of the introduction of C-SPAN, and thus greater public attention, finding that this leads to a notable rise in the use of victimhood narratives. In the Northern Ireland chapter, I explored the roles of legislator characteristics, identity salience, and competitive victimhood. The results show that exclusive victimhood narratives are used in a competitive, often oppositional manner toward outgroup claims, with less conclusive findings around legislator characteristics and ethnic saliency. My findings suggest that legislator identity indicators, public attention, and political competition are central in understanding the use of victimhood narratives in legislatures. I also demonstrate that quantitative text analysis can effectively identify and measure victimhood narratives in two diverse legislative contexts.
APPROVED
Keywords: Collective Victimhood; United States; Northern Ireland; Quantitative Text Analysis; Legislative Speech